The Republican Party : the story of the Grand Old Party - Anderson, Dale. (Minneapolis, MN : Compass Point Books, 2007)
Describes the history of the Republican Party from its origin in 1854 to today. Includes a listing of various political issues and the positions held by both the Republican and Democratic Party.
A surprising election -- The Republicans win the White House -- The party of freedom -- The party grows and changes -- Successes and failures -- The new Republican Party -- The Republican Party today.
6-8
6-8
1130L
Accelerated Reader AR
Includes index and glossary.
Includes bibliographic references.
Keywords: Republican Party; Political parties; United States -- Politics and government